INTERNATIONAL LOBBYING AS EFFECTIVE MECHANISM OF ECONOMIC DIPLOMACY (in the context of realization of national interests) - TATARENKO, Nataliia; POBOCHENKO, Lesia; PROKOPIEVA, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the problem of development of economic diplomacy, enrichment of its tools in accordance with modern global realities and needs of countries. The authors propose their own methodology of analysis, specifying the categorical apparatus. In particular, economic diplomacy is interpreted as official activity of states and international organizations, which exclude negotiation processes carried out by various non-state international business institutions including TNCs.In this context, the special role of economic diplomacy is emphasized which include coordination (subordination of private economic activity to national interests), consolidation and catalyzation. These functions of economic diplomacy provide additional possibilities to defend national economic interests and impose control over the international economic activity of economic agents, ensure synergy of national and private interests and create favorable conditions for their implementation and acceleration of the processes of achieving goals (catalyst function). The consolidating function of economic diplomacy is to combine the capabilities and efforts to ensure success in international negotiation processes at the state level represented by diplomats and authorized officials, private economic agents, media, think tanks, digital platforms, NGOs, cultural and scientific figures with their broader capabilities, methods of influencing ideology, shaping public opinion, etc.Among the methods and tools of economic diplomacy, the authors distinguish those acceptable for official activities, codified by international and diplomatic law. However, the article notes that political (propaganda) methods and lobbying activities are also a component of economic diplomacy, if they do not go beyond the outlined boundaries of diplomatic activity. More effective methods of influencing the economic policy of foreign countries and the formation of a favorable international economic environment to promote the interests of national business and the state can be used by economic and non-economic agents of influence. Special attention in this study is paid to international lobbying as one of the instruments of influence on the formation of a favorable environment for national business - the combination of diplomatic efforts of the state and lobbying capabilities of business is considered by the authors as the basis for ensuring synergy of interests in the context of the tasks of the country's foreign economic policy.The article also considers mechanisms for countering the corruption component of international lobbying.
Keywords: foreign economic policy; economic diplomacy; functions of economic diplomacy; national economic interests; interests of subjects of international economic activity; synergy of economic interests; catalytic nature of economic diplomacy; subjects and objects of economic diplomacy; methods and tools of economic diplomacy; international economic lobbying; methods and tools of lobbying; mechanisms for countering corruption in lobbying